Survey of Compliance with Radiation Protection Standards in Diagnostic Imaging Centers of Khuzestan Province in 2015 - farshid mahmoudi; Amirhossein Davoudian talab; Gholamreza badfar (Mazandaran University of Medical Sciences, 2017)
Introduction and purpose: The growing use of ionizing radiation in disease diagnosis necessitaes the appropriate use of devices and awareness regarding the principles of radiation protection. With appropriate adoption of personal protection equipment and compliance with the existing regulations in relation to protection of the buildings where sources of ionizing radiation are located in, the adverse effects of radiation can be curtailed to a great extent. Methods: In this descriptive, analytical, cross-sectional study, we investigated the rate of compliance with radiation protection standards of 45 radiography rooms in 32 diagnostic imaging centers in Khuzestan Province, Iran, 2015. The centers were chosen through random cluster sampling method. The data were obtained using open-ended interview and a checklist designed based on the recommendations of the International Commission for Radiation Protection and Atomic Energy Organization of Iran. Results: The compliance rates with regard to radiology room, radiology equipment, darkroom, and radiographer’s protection were 80.76%, 80.47%, 69.28%, and 93.12%, respectively. Maximum and minimum rates of compliance with the standards were related to performance of the cassette tray (100%) and hopper status (25%), respectively. Comparison of public and private imaging centers in terms of safety standards showed no significant differences (P>0.05).Conclusion: The observance of the radiation protection standards in Khuzestan Province was in a relativly desirable condition. However, there are some shortcomings in compliance with the principles of protection in the darkroom. In this regard, with recommend adopting protection measures such as timelyreplacement of processing solution, appropriate ventilation of darkroom, provisionof protection equipment and appliances, and protection training required for entering the darkroom.